The Influence Of Promotion, Service Quality, And Price Perceptions On Repurchase Decisions (Revisit) For Consumers Of Coca-Cola Soft Drinks In Bekasi District - Suryanegara, Raihan Hakim; Purnamasari, Pupung (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Among the various types of soft drinks, carbonated beverages are highly favored by the population. According to the Top Brand Award data, Coca-Cola holds the top position in the carbonated beverage category. This research aims to examine and elucidate the impact of promotional activities on Coca-Cola products on repeat purchase decisions partially. It also aims to test and explain how service quality of Coca-Cola products influences repeat purchase decisions partially, and to examine and explain how price perception of Coca-Cola products affects repeat purchase decisions partially. Furthermore, it aims to test and explain how promotional activities, service quality, and price collectively affect repeat purchase decisions. The sampling method employed in this study is non-probability sampling, specifically purposive sampling. The survey sample comprises a total of 101 respondents aged between 17 and 45 from Bekasi Regency. For data analysis, this research utilizes Structural Equation Modeling (SEM) with the support of SmartPLS 3.0 software. This tool is used to test the validity and reliability of instruments, assess model adequacy, and examine the proposed relationships within the theoretical framework.